2003
DOI: 10.1103/physrevd.67.043510
|View full text |Cite
|
Sign up to set email alerts
|

Isotropization in brane gas cosmology

Abstract: Brane Gas Cosmology (BGC) is an approach to unifying string theory and cosmology in which matter is described by a gas of strings and branes in a dilaton gravity background. TheUniverse is assumed to start out with all spatial dimensions compact and small. It has previously been shown that in this context, in the approximation of neglecting inhomogeneities and anisotropies, there is a dynamical mechanism which allows only three spatial dimensions to become large. However, previous studies do not lead to any co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 20 publications
1
93
0
1
Order By: Relevance
“…From (16) we find that the zero mode energy and pressure 1 of the string gas in D − 1 compact dimensions can be written as, E = 3µN (3) e λ + 3µM (3) e −λ + 6µN (6) e ν + 6µM (6) e −ν ,…”
Section: String Sources and T-dualitymentioning
confidence: 99%
See 1 more Smart Citation
“…From (16) we find that the zero mode energy and pressure 1 of the string gas in D − 1 compact dimensions can be written as, E = 3µN (3) e λ + 3µM (3) e −λ + 6µN (6) e ν + 6µM (6) e −ν ,…”
Section: String Sources and T-dualitymentioning
confidence: 99%
“…A possible resolution to this problem was suggested in [1] (see also [2]) and has since been generalized to include more realistic background geometries and the inclusion of branes [3,5,6]. The authors of [1] argued that, by considering the dynamics of the winding and momentum modes of the strings, a new symmetry specific of string theory, namely t-duality, could eliminate the big-bang singularity and also explain the dimensionality of space-time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems reasonable that (23) will hold approximately even if branes are included in the thermal gas of strings. See [11,12,13,16,17,19,21,22,25,26] for some work relevant to time evolution in brane gases. Similarly, allowing the shape moduli of the spatial torus and the various form fields of supergravity to be nontrivial may alter the qualitative behavior of the dilaton, such as by providing a potential (for a review of flux compactifications with stabilized dilaton, see [44]).…”
Section: Estimating Interaction Rates From Cosmologymentioning
confidence: 99%
“…One important generalization has been including branes in the early universe gas of strings [4,5,6,7], and other spacetime topologies have also been considered [8,9]. Starting with [2,3], a number of authors have examined the cosmological equations of motion appropriate to string gases as well as brane gases [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. In particular, [25,26] showed that interesting cosmological dynamics happen when the expanding dimensions are still near the string scale, and [7,27,28,29] have begun to examine the effects of nontrivial backgrounds of fields other than the metric in the low energy supergravity.…”
Section: Introductionmentioning
confidence: 99%
“…One intriguing possibility is that extended objects play a vital role in explaining the asymmetry. This is the idea behind brane gas cosmology [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%